Investigating the impact of oral health on pregnancy and offspring outcomes: protocol for the Lifetime Impact of ORal heAlth (LIORA) cohort study. Issue 11 (29th November 2022) - Zhao, Mei-Ling; Zhang, Feng-Jing; Jiang, Wen-Rong; xia, yinyin; Chen, Chang; Zhang, Ting; Han, Ting-Li; Yu, Xin-Yang; Mei, Peter; Zhang, Hong-Mei; Jin, Xin; Novakovic, Boris; et al.
Abstract : Introduction: Oral health is a fundamental component of well-being, and is closely associated with overall health and quality of life. Oral health may also affect the next generation. The children of mothers with poor oral health are likely to also have poor oral health as they go through life. We aim to investigate associations between maternal oral health and general health, pregnancy outcomes, offspring oral health and offspring general health. Methods and analysis: The Lifetime Impact of Oral Health study is a prospective, observational cohort study being done at a single centre in Chongqing, China. A total of 1000 pregnant women will be recruited in their first trimester (11–14 weeks gestation). After obtaining informed consent, general and oral health assessments will be undertaken. Maternal lifestyle, demographic data and biospecimens (blood, hair, urine, nail clippings, saliva, dental plaque, buccal, vaginal and anal swabs) will be collected. Pregnancy outcomes will be recorded at the time of delivery. Cord blood and placenta samples will be collected. The offspring will be followed up for general and oral health examinations, neurodevelopmental assessments and biospecimen (dental plaque, saliva, buccal swabs, exfoliated primary dentition, urine, hair, nail clippings) collection until they are 15 years old. Biological samples will undergo comprehensive metabolomic, microbiome and epigenome analyses. Associations between maternal oral health and general health, pregnancy outcomes, offspring oral health and offspring general health will be investigated and the underlying mechanisms explored. Ethics and dissemination: This project has been approved by the Research Ethics Committee of the Affiliated Hospital of Stomatology of Chongqing Medical University (CQHS-REC-2021 LSNo.23). Participants will be required to provide informed consent to participate in the study. Dissemination of findings will take the form of publications in peer-reviewed journals and presentations at national and international conferences. Trial registration number: ChiCTR2100046898.